Carbon and nutrient mineralisation dynamics in aggregate-size classes from different tillage systems after input of canola and wheat residues. (January 2018) - Sarker, Jharna Rani; Singh, Bhupinder Pal; Cowie, Annette L.; Fang, Yunying; Collins, Damian; Dougherty, Warwick J.; Singh, Brajesh K.
Abstract: Aggregate-size classes may have different microbial accessibility and therefore different decomposability of aggregate-associated soil organic matter (SOM). However, processes and mechanisms of soil organic carbon (SOC) mineralisation and availability of nutrients [nitrogen (N), phosphorus (P) and sulphur (S)] in different aggregate-size classes, and particularly, the interaction of aggregates with tillage intensity and crop residue type in contrasting soils is poorly understood. Soil samples from conventional tillage (CT) and reduced tillage (RT) systems under mixed wheat–pasture farming, and no-till (NT) under continuous cereal–cover cropping in a Luvisol, and from CT and NT under continuous wheat cropping in a Vertisol, were separated into three dry aggregate classes of different sizes [mega-aggregates (>2–6.5 mm), macro-aggregates (0.25–2 mm) and micro-aggregates (<0.25 mm)]. Two residue types (canola and wheat stem; δ 13 C 124 and 460‰, respectively) were added into each of the three aggregate class samples from Luvisol (δ 13 C −24.7‰) and Vertisol (δ 13 C −18.5‰). Total CO2 -C, δ 13 C in CO2 -C, microbial biomass C (MBC), and plant available N, P and S were measured periodically during the 126-day incubation. The results showed that crop residue input increased native SOC mineralisation ( via positive priming), MBC and microbial metabolic quotient in all three aggregate-size classes from different tillage systems in both soils. Native SOC mineralisation was 1.5–3.7 and 0.6–2.8 times higher in the canola and wheat residue-amended ( cf . control, non-amended) aggregates, respectively. Native SOC mineralisatiion and MBC were higher in the macro- and micro- than mega-aggregates in both soils. However, priming of native SOC mineralisation, relative to the control, was similar across the aggregates, except for the CT in the Luvisol where priming was higher in the macro- than micro- and mega-aggregates. Native SOC mineralisation among the aggregate-size classes was 26–114% higher under CT or RT cf . NT in the Luvisol but was similar under CT and NT in the Vertisol. Net available N was significantly higher in the residue-amended than the control aggregates, particularly in the CT and/or RT versus the NT at day 30 only, and mainly in the Luvisol. Further, substantial amounts of available P and S were released from the residue-amended versus the control aggregates at day 126, with Vertisol releasing 2–3 times more available P than Luvisol. In conclusion, our findings showed the importance of returning crop residues to enhance nutrient availability from all aggregate-size classes in different soils and farming systems. In particular, the tillage ( versus no-till) and canola ( versus wheat) residue induced a greater release of nutrients, generally in the pattern of micro- ≥ macro- > mega-aggregates. Clearly, the input of crop residues enhanced the release of SOM-bound nutrients, possibly via positive priming, and may have mobilised mineral-bound nutrients, such as P and S in each aggregate-size class, with tillage intensity and soil type modulating these processes. Highlights: Tillage intensity, aggregate-size & residue type impacted nutrient release in soils. SOC priming in aggregates was quantified after adding 13 C-labelled crop residue. Canola vs. wheat residue input in till cf . no-till caused higher aggregate-SOC priming. Net available N, P & S were higher in micro- and/or macro- than mega-aggregates. Canola vs. wheat residue input in till cf . no-till released more N, P & S in aggregates.